THE SELF IN THE OTHER : PSYCHOANALYTIC TRACING OF NARCISSISM IN LOVE RELATIONSHIPS OF LOKI FROM MCU AND THEODORE FROM HER - Sreehari S; Purushothaman, Kavya (International Journal of Research -GRANTHAALAYAH, 2025)
Narcissism originated from the Greek mythological story of Narcissus, a young man who fell in love with the reflection of himself, and is based on self-obsession, entitlement, and a desire for admiration. This essay examines a psychoanalytic interpretation of problematic love affairs in narcissistic individuals. This investigation is carried out using characters of Loki from the Marvel Cinematic Universe and Theodore from Her. The paper studies how these love relationships align with narcissistic cathexis, introduced by Sigmund Freud, where individuals direct their libidinal energy inward, and Otto Kernberg’s theory of pathological narcissism. The study analyzes how these characters, in pursuing emotional intimacy, reveal their unresolved desires for validation and control. The evolution of the individuals in these relationships also suggests that the condition is affected by the early developmental experiences, leading to a distorted self-concept.